What Strategy to Develop Female Leadership to Support a Company’s Sustainability in State Owned Enterprises (SOES)? - Dewi, Nina Kurnia; Suroso, Arif Imam; Fahmi, Idqan; Syarief, Rizal (School of Business, Bogor Agricultural University (SB-IPB), 2024)
This paper was to explain the result of current study and use it to further explore the characteristics that need to be improved by female leaders in Indonesian State-Owned Enterprises (SOEs) to support the company’s sustainability. The research method was quantitative-based and used an online survey on all female leaders in Indonesian SOEs. It was found that female leaders in SOEs had characteristics of Visionary and Organic Leadership, with indicators of ability to decision making, power distance between leaders and follower, key organizational players, sources of organizational commitment and responsibility and leadership situations. Using Partial Least Square-Structural Equation Modeling (PLS-SEM) and software WarpPLS, the study discovered that visionary female leadership had no impact on the company’s sustainability. Nevertheless, by fully mediating business competency and partially mediating of organizational competency, there was a significant impact of Female Visionary Leadership on Companies’ Sustainability. Based on the model from the current study of the influece of female leadership on corporate sustainability, this study developed a strategy for the development of women leadership by providing indicators that should be increased in women leaders. Using AHP method, it was necessary to develop the character of Visionary Female Leadership in Indonesian SOEs by increasing the source of organizational commitment and responsibility, leadership skill and ability to make decision. Keywords: female leadership, visionary leadership, organizational commitment, leadership skills ability in decision making